The Influence of Learning Styles on Employee Development and Training Effectiveness - Radha, P.; Rajan, Raji; Ranganaki, Usha (Academic Journal of Simara, 2026)
Learning styles individual preferences for acquiring, processing, and retaining information (e.g., visual, auditory, kinesthetic) profoundly influence employee development when integrated into training programs. This enhances skill acquisition, engagement, and performance amid diverse workforce needs. The article reviews learning style categorizations, aligns training modalities (e.g., e-learning, classroom instruction, hands-on practice) with them, and evaluates blended approaches combining traditional and digital methods. It examines technology’s role (e.g., LMS, AI platforms) in delivering personalized content, drawing on case studies and empirical evidence to demonstrate impacts on satisfaction, retention, and outcomes. Challenges include oversimplification risks and evaluation needs; recommendations guide HR/L&D professionals toward adaptive, inclusive strategies fostering continuous growth.